OP0088 Categorization of Baseline Systemic Activity at Diagnosis Using the Essdai Disease Activity States (DAS) in Primary Sjögren Syndrome: Association with Poor Outcomes. (9th June 2015) - Brito Zeron, P.; Kostov, B.; Solans, R.; Fraile, G.; Caravia-Durán, D.; Maure, B.; Rascόn, F.-J.; Villar-Navas, B.; Ripoll, M.; Pinilla, B.; Fonseca, E.; Akasbi, M.; et al.
Abstract : Objectives: To score systemic activity at diagnosis and correlate baseline activity classified according to the ESSDAI disease activity states with poor outcomes in a large cohort of patients with primary Sjögren syndrome (SS). Methods: We include 1216 consecutive patients who fulfilled the 2002 classification criteria for primary SS. The clinical and immunological characteristics and level of systemic activity were assessed at diagnosis as predictors of poor outcomes (lymphoma and death) using Cox proportional-hazards regression analysis adjusted for age at diagnosis. European systemic activity index (ESSDAI) scores were retrospectively calculated at diagnosis. Disease activity states (DAS) were defined according to the baseline ESSDAI score (low DAS for an ESSDAI <4, moderate DAS for an ESSDAI between 5 and 13, and high DAS for an ESSDAI higher than 13). Results: After a mean follow-up of 114 months, 52 (4%) patients developed hematological neoplasia and 139 (11%) died. The most frequent systemic activity reported at the time of SS diagnosis included articular (37%), biological (35%), hematology (30%) and glandular (24%) involvements. At diagnosis, 138 (11%) patients showed a high DAS, 385 (32%) a moderate DAS, 422 (35%) a low DAS and 266 (22%) had no systemic activity (ESSDAI =0). No significant differences in the main baseline features were found according to the DAS except for the age at SS diagnosis, which was higher in patients with a high DAS (57 yrs vs 53 yrs for moderate DAS, 54 for low DAS and 56 for no activity, p=0.019). Patients who showed a high DAS at diagnosis of SS developed more frequently hematological neoplasia and had a poor survival in comparison with patients who showed no systemic activity (ESSDAI =0) (19% vs 2%, p<0.001, and 19% vs 11%, p=0.032, respectively). Patients with a high-DAS at diagnosis developed more frequently cancer in comparison with those without high baseline activity (21% vs 10%, p<0.001); however, a high DAS was related to a higher frequency of hematological neoplasia but to a lower frequency of solid neoplasia (18% vs 2.5%, 2.9% vs 7.5%, p<0.001). Conclusions: Categorization of baseline systemic activity using the ESSDAI disease activity states at diagnosis of primary Sjögren syndrome is useful to identify patients with a high risk of developing poor outcomes; patients who present at diagnosis with ESSDAI≥14 (high DAS) should be considered a high-risk population and should be followed more closely than those with no systemic activity. Disclosure of Interest: None declared